2014
DOI: 10.1111/liv.12632
|View full text |Cite
|
Sign up to set email alerts
|

Two‐year outcomes in initial survivors with acute liver failure: results from a prospective, multicentre study

Abstract: BACKGROUND The long-term clinical outcomes in initial survivors with acute liver failure (ALF) are not well known. AIMS The aim of the current study is to provide an overview of the 2 year clinical outcomes amongst initial survivors and liver transplant (LT) recipients that were alive 3 weeks after enrollment in the Acute Liver Failure Study Group (ALFSG). METHODS Outcomes in adult ALFSG patients that were enrolled between 1998 and 2010 were reviewed. RESULTS 2-year patient survival was significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 36 publications
2
50
1
Order By: Relevance
“…The observed association of persistent liver injury with increasing patient age is not surprising. Studies of ALF patients have demonstrated that older subjects are more likely to die or experience greater morbidity presumably due to impaired hepatic regeneration (14). Older age is a strong determinant of developing chronic hepatitis C virus infection after initial exposure and older patients demonstrate greater evidence of hepatic inflammation and fibrosis progression during follow-up (15, 16).…”
Section: Discussionmentioning
confidence: 99%
“…The observed association of persistent liver injury with increasing patient age is not surprising. Studies of ALF patients have demonstrated that older subjects are more likely to die or experience greater morbidity presumably due to impaired hepatic regeneration (14). Older age is a strong determinant of developing chronic hepatitis C virus infection after initial exposure and older patients demonstrate greater evidence of hepatic inflammation and fibrosis progression during follow-up (15, 16).…”
Section: Discussionmentioning
confidence: 99%
“…With the higher incidence of psychiatric illness and prior suicide attempts in these patients, long-term survival can be affected by repeated suicide attempts, substance abuse, and nonadherence to medications (Cooper et al 2009;Karvellas et al 2010). A review of the Acute Liver Failure Study Group data showed better long-term survival following acetaminophen overdose with transplantation than with spontaneous recovery, possibly due to the need for closer follow up with healthcare professionals after transplantation (Fontana et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Overall hospital survival increased from 17% in 1973–1978 to 62% in 2004–2008 at a single center in the UK [3]. In a multicenter registry from the USA, in 1998–2010 ALF 2-year survival has been reported as 92% for LT recipients, 90% for paracetamol-related spontaneous survivors, and 76% for non-paracetamol-related spontaneous survivors [9]. …”
Section: Introductionmentioning
confidence: 99%